Antecedents of Psychological Empowerment and The Impact on Nurses Burnout - Jason Jason; Ferdi Antonio (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: The health and well-being of nurses are deteriorating due to several factors such as complicated nursing practices, high patient demands, heavy workload, all of which result in frustration and lead to burnout, especially emotional exhaustion. Purpose: The purpose of this study was to examine the effect of the antecedents of psychological empowerment on burnout in nurses who worked at the COVID-19 Hospital XYZ in Tangerang during the pandemic. Methods: This research is a quantitative research with survey. PLS-SEM was used to analyse empirical data obtained through simple random sampling. There were 80 samples collected and analysed through questionnaire that had been distributed online. The results showed that six of the eight variables of quality of work life, as well as psychological empowerment mediating variables, had a significant negative effect on burnout (t-statistic > 1.645). Results: The direct influence on psychological empowerment was found to be the strongest from the opportunity to develop human capital and adequate and fair compensation (coefficient: 0.627 and 0.361). It was found that there was a negative impact of psychological empowerment on burnout (-0.756), thus the results of this study support the theory that the quality of work life can increase psychological empowerment among nurses, as well as show a new application to the psychological empowerment of nurses. Conclusion: This research model has moderate predictive accuracy and medium predictive relevance, so it can be developed in further research. There are managerial implications obtained from the findings of this study related to duration of work per week, work environment, granting of autonomy, as well as recommendations for future researchers regarding sample size and geographic coverage.